Observation of the natural characteristics of the oviposition of Culex (Melanoconion) Grupo Pilosus (Diptera: Culicidae) - Gomes, Almério de Castro (1998)
Eggs of Culex (Melanoconion) Grupo Pilosus were found in three oviposition traps set in the toilet of a Bus Station in Joinville city, State of Santa Catarina, Brazil, during a surveillance study of Aedes aegypti. The intrinsic characteristic of group oviposition not directly on the water was confirmed.